Hambatan Yang Dihadapi Guru Dalam Menerapkan Literasi Numerasi Di Sekolah Dasar - Ayuningtyas Nurhayati Lukito; Adel Meru Aulia; Windriani Ulfa Subekti; Wita Puspita Sari; Tia Citra Bayuni (Arfah BHMS Foundation, 2026)
This study aims to analyze the obstacles faced by teachers in implementing numeracy literacy in elementary schools. Numeracy literacy is an important skill that students must have in order to understand, interpret, and use mathematical concepts in everyday life. However, its implementation still faces various obstacles, such as limited teacher competence, lack of facilities and infrastructure, inadequate learning media, and minimal numeracy literacy training for educators. These conditions have an impact on low student numeracy skills and suboptimal literacy-based learning in elementary schools. This study used a descriptive quantitative approach with a survey method through a Likert scale questionnaire distributed online to elementary school teachers in the Bekasi area. The data were analyzed descriptively to describe the types and levels of obstacles experienced by teachers in the learning process. The results of the study provide a comprehensive picture of the factors that hinder the implementation of numeracy literacy and form the basis for formulating strategies to improve the quality of learning. This study contributes to schools and policy makers in designing teacher training programs, developing innovative learning media, and strengthening a culture of numeracy literacy to improve the quality of basic education.